THE RELATIONSHIP BETWEEN THE DURATION OF PLAYING ONLINE GAMES AND INCIDENTS CARPAL TUNNEL SYNDROME IN MALE STUDENTS AT SMAN XTHE RELATIONSHIP BETWEEN THE DURATION OF PLAYING ONLINE GAMES AND INCIDENTS CARPAL TUNNEL SYNDROME IN MALE STUDENTS AT SMAN X - Dewi Zuniawati; Andyanita Hanif Hermawati (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Background: Online games are games played using an internet connection and have recently become popular among teenagers. Playing online games for long periods can have negative health effects such as headaches, back pain, and carpal tunnel syndrome. Carpal tunnel syndrome is a collection of symptoms of pain, tingling, and numbness in the wrist area. The purpose of this study was to determine the relationship between the duration of online game play and the incidence of carpal tunnel syndrome in male students at SMAN X.. Method: The research design used was correlational analytic with a cross-sectional approach. The population of this study was 105 people, and 51 people were sampled using a purposive sampling technique. The research instruments were a questionnaire sheet regarding the duration of playing online games and the Boston Carpal Tunnel Questionnaire. Data processing included editing, coding, scoring, tabulating, and data analysis using the non-parametric chi-square test with the SPSS program. Result: The results of the study showed that 31 respondents (60.8%) had a frequent online game playing duration and 36 respondents (70.6%) experienced symptoms of carpal tunnel syndrome. From the results of the chi-square statistical test, the P Value = 0.003 was smaller than the value α = 0.05 (0.003 < 0.05), which means there is a relationship between the duration of playing online games and the incidence of carpal tunnel syndrome in male students at SMAN X. Conclusion: Teenagers experiencing symptoms of carpal tunnel syndrome are advised to limit gaming to 2–3 hours per day. Carpal tunnel syndrome symptoms can also be minimized by using soft wrist pads and regularly engaging in physical exercises such as opening and closing the fingers and rotating the wrist several times.